Continuous higher order sliding mode control with adaptation of air breathing hypersonic missile. (20th January 2016) - Yu, Polk; Shtessel, Yuri; Edwards, Christopher
Summary: Hypersonic missile control in the terminal phase is addressed using continuous adaptive higher order sliding mode (AHOSM) control with adaptation. The AHOSM self‐tuning controller is proposed and studied. The double‐layer adaptive algorithm is based on equivalent control concepts and ensures non‐overestimation of the control gain to help mitigating control chattering. The proposed continuous AHOSM control is validated via simulations of a hypersonic missile in the terminal phase. The robustness and high‐accuracy output tracking in the presence of matched and unmatched external disturbances and missile model uncertainties is demonstrated. Copyright © 2016 John Wiley & Sons, Ltd.